The Impacts of Climate Change on Chinese Agriculture - Ju, Hui; Liyong, Xie; Zhanyun, Mia (Annals of Arid Zone, 2016)
The future climate change will most likely have adverse impacts on Chinese agriculture, especially the cropping system (CS). With a predicted temperature rise of 1.4Â°C and precipitation increase of 4.2% by 2050, current double cropping system (DCS) in most regions of China wili be replaced by different combinations . of triple-cropping system (TCS). The boundary of TCS will extend northwards as much as 500 km, from the Yangtze River Valley to the Yellow River Basin. The region of DCS will move to the central part of current single cropping system (SCS) region, and the area of SCS will decrease by 23.1 %. Climate warming will also affect the layout of China's main crop varieties. In the north of China, winter wheat will be replaced by semi-winter wheat; high-temperature-resistant rice varieties will gradually extend to the northern rice area, and the early ripening varieties in the northeast will be gradually replaced by middle and late ripening varieties. If no measures are taken to adapt to these changes, by the middle of the 215t century the production of several crops, including wheat, rice and com, will decrease by a maximum 23%, and the changes in production will vary among different regions. There will be significant reduction in the main producing region, but smaller reduction or even a slight increase in some minor regions. The production of corn and rice in the northern part of the northeastern region will increase, and so will wheat and com in the north of northeast China, benefiting from the precipitation increase in the future. By the 2080s the production of rain-fed wheat will decrease by 23.7%, and the rain-fed rice by 12.7%, whereas the rain-fed corn will increase. Compared with the current production, the irrigated wheat, corn and rice will reduce by 20.2%, 24.7% and 5.4%, respectively. As a result of climate change, the C/N ratio of crops in China will increase and the protein content and quality will decrease. The use of pesticide and weedicide will increase due to more prevalence of crop pests, diseases and weeds. Climate warming will increase the evaporation losses during the crop growing season, and increase the need for irrigation water. Key words: Climate change, Chinese agriculture, impacts, crop production, food securi ty.